THE INFLUENCE OF SERVICE QUALITY ON REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION MEDIATION AT BCE EXPRESS - Mega Jayanti; Arbi Siti Rabiah H.M (Pedagogic Research-Applied Literacy Journal, 2025)
The development of the service industry currently plays an important role in contributing to the country's economy. One type of service company is a goods delivery service company. This study aims to determine the effect of service quality on repurchase intention through customer satisfaction as a mediating variable at BCE Express Green Lake City. This research used a quantitative approach by using probability sampling and a simple random sampling technique, which was processed through path analysis. Samples in this study amounted to 100 respondents. The results achieved in this study are that service quality has a significant positive effect on customer satisfaction, service quality has a significant positive effect on repurchase intention, and customer satisfaction has a significant positive effect on repurchase intention. Another finding is that service quality has a significant positive effect on repurchase intention through the mediation of customer satisfaction.